DIAGNÓSTICO LABORATORIAL DA AMEBÍASE:Detecção e Diferenciação Simultânea da Entamoeba histolytica e Entamoeba dispar por Ensaio Imunoenzimático(ELISA) e Multiplex-PCR - Santos, Helena Lúcia Carneiro (2005)
Amebiasis is defined as an infection caused by Entamoeba histolytica. However, precise differentiation between E. histolytica and Entamoeba dispar, which are morphologically identical species, is essential for treatment decision, prevention of the invasive disease and public health. The purpose of the present study was to evaluate a Multiplex-PCR for detection and differentiation of E. histolytica from E. dispar. Microscopic examination of stools using the coprotest kit, detection of stool antigen using a commercial enzyme-linked immunosorbent assay kit and a home made Multiplex-PCR, were compared for the diagnosis of amebiasis infection. The Multiplex-PCR was standardized using stool samples with parasites obtained from standard cultures. Afterwards, 127 stool samples obtained from individuals living in two villages of the state of Rio de Janeiro were tested and the results were compared. Analysis of the 127 stools samples by microscopy examination demonstrated that only 27 (21%) samples were positive for E. histolytica /E. dispar complex. Among these stool samples, 12 were positive by Multiplex-PCR, with nine presenting the diagnostic fragment characteristic of E. dispar (96 bp) and three presenting diagnostic fragment of E. histolytica (132 bp). Among the negative samples detected by microscopic examination, three were positive for E. dispar and one was positive for E. histolytica by Multiplex-PCR. This denotes that Multiplex-PCR was more efficient than microscopic examination when single stool samples were analyzed. The results obtained by detection of E. histolytica antigen were in agreement with those obtained by the multiplex-PCR. Statistical analyses comparing coproantigen ELISA with Multiplex-PCR results were not done because of the low number of E. histolytica cases. The overall results indicate the need to use more sensitive methods for the diagnosis of amebiasis infection and the importance of using specific techniques for the differentiation between E. histolytica and E. dispar.